ANALISIS PENGARUH PEMBERDAYAAN PERENCANAAN KOMUNIKASI TERHADAP ADVOKASI HASIL PENELITIAN MAHASISWA ( STUDI PADA MAHASISWA TINGKAT AKHIR DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DARMA AGUNG MEDAN 2017 - Rita Vinolia Aruan; Elok Perwirawati (Jurnal Darma Agung, 2018)
In the world of education, students in particular need a clear especially in mentoring activities – research activities as well as the completion of the final tasks.Remembering things are required of a planning strategy communication between parties as well as the campus professors to engage in advocacy or mentoring on students ' research activities and thus expected research results the better students and qualified again.The purpose of this research is to know the generally Influence the planning of communication Towards Empowerment Advocacy Research students (studies on the final Level Students majoring in Communication Fisipol Darma Agung, Medan 2017).Research methods used in this research is quantitative methods.The location of the research carried out in Fisipol Darma Agung, Medan 2017. The population is all students Majoring Fisipol Darma Agung, Medan 2017 which is being compiled final project as many as 54 people.The number of sample study was 54 people (total sampling). Data analysis includes the Univariate Analysis, Bivariat and multivariate. Research results show that empowerment process approach, empowerment, empowerment approach system approach to technological, economical approach to empowerment and empowerment evaluation approach has the influence on the results of advocacy research students.This is indicated by the value that the t-test for independent samples F = 18,796, value of R = 0,646, t calculate = 6.095 and value adjusted r-square = 0.405